Action Flow in Obsessive-Compulsive Disorder Rituals: a model based on Extended Synergetics and a Comment on the 4th Law - Frank, Till D (JOURNAL OF ADVANCES IN PHYSICS, 2014)
The flow of actions in rituals of obsessive individuals is discussed from a nonlinear physics perspective. An amplitude equation model based on extended synergetics is studied. The amplitude dynamics describes both the behavioral actions and the experienced emotions during obsessive-compulsive disorder rituals. The model suggests that in addition to the behavioral and emotional levels that are accessible to external observation and self-reports there are hidden levels captured by parameter dynamics that determine the action flow in obsessive-compulsive disorder rituals. The model can also be used to discuss on the mechanistic and behavioral levels differences between purposeful and purposeless rituals. While purposeful rituals involve a continuous control of the emotional level over the behavioral level, purposeless rituals do not exhibit such a continuous control mechanism. Finally, it is argued that the selection principle determining the action flow in obsessive-compulsive disorder rituals is consistent with the so-called 4th law of non-equilibrium phase transitions in animate and inanimate systems